Paradise gardens the world's most beautiful Islamic gardens - Don, Monty (Two Roads imprint of John Murray Press, 2018)
An exploration of the beauty of Islamic paradise gardens around the world with text by Monty Don stunningly illustrated with photographs by Derry Moore. A complement to the BBC2 TV series, Monty Don's Paradise Gardens.